2012
DOI: 10.1016/j.nepr.2012.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The ‘follow-through’ experience in three-year Bachelor of Midwifery programs in Australia: A survey of students

Abstract: Despite these challenges, there were significant learning opportunities. Future work and research needs to ensure than an integrated approach is taken to enhance learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 11 publications
3
28
0
3
Order By: Relevance
“…This study also confirms that CoC experiences promote the development of partnerships with women, prepares students to work in CoC models, and is highly valued by them. These results align closely with previous research (Aune et al, 2011;Gray et al, 2012;Gray et al, 2013;McLachlan et al, 2013). CoC experiences embed midwifery student education in the 'real world' of care for women throughout their continuum of care.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study also confirms that CoC experiences promote the development of partnerships with women, prepares students to work in CoC models, and is highly valued by them. These results align closely with previous research (Aune et al, 2011;Gray et al, 2012;Gray et al, 2013;McLachlan et al, 2013). CoC experiences embed midwifery student education in the 'real world' of care for women throughout their continuum of care.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, most students had completed more than their minimum required continuity of care experiences. Previous studies identified that recruiting women was a major challenge with CoC experiences (Gray et al, 2012;Gray et al, 2013;McLachlan et al, 2013). RPMEP arrangements whereby students are placed within CoC midwifery models resulted in relatively seamless recruitment of women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New graduate midwives, those in their first‐year post‐graduation, have not historically worked in continuity of care models despite being prepared to work across the scope of midwifery practice from their degrees (Gray et al . , Cummins et al . ).…”
Section: Introductionmentioning
confidence: 99%